A prospective evaluation of clinical and genetic predictors of weight changes in breast cancer survivors. Issue 13 (14th February 2017) - Sadim, Maureen; Xu, Yanfei; Selig, Katharina; Paulus, Julie; Uthe, Regina; Agarwl, Surbhi; Dubin, Iram; Oikonomopoulou, Panagiota; Zaichenko, Lesya; McCandlish, Silvia Aki; Van Horn, Linda; Mantzoros, Christos; et al.
Abstract : BACKGROUND: Postdiagnosis weight gain in patients with breast cancer has been associated with increased cancer recurrence and mortality. This study was designed to identify risk factors for weight gain and create a predictive model to identify a high‐risk population for targeted interventions. METHODS: The weight of 393 patients with breast cancer from the Northwestern Robert H. Lurie Cancer Center was measured over a 2‐year period from diagnosis, with body mass index (BMI) change over 18 months as the primary endpoint. Demographics, clinical factors, treatment methods, as well as tumor characteristics were also recorded; and a lifestyle questionnaire was conducted. Blood samples were genotyped for 16 single nucleotide polymorphisms in FTO, adiponectin pathway genes ( ADIPOQ, ADIPOR1 ), and FNDC5 . Serum leptin, adiponectin, and irisin levels also were measured. RESULTS: Mean ± standard deviation 18‐month BMI changes were 0.68 ± 1.42, 0.98 ± 1.62, 0.79 ± 1.74, and −0.44 ± 1.58 kg/m 2 for patients ages <40, 40 to 49, 50 to 59, and ≥60 years, respectively. The optimal multivariable model for 18‐month BMI change contained the predictors age, height, and endocrine therapy, but only age was statistically significant, with a 0.04 kg/m 2 increase in 18‐month BMI change per younger year of age. Single nucleotide polymorphisms in ADIPOR1, FTO, and FNDC5 were associated with 18‐month BMI change, and the first 2 remained significant after adjusting for the optimal clinical model (all P < .05). CONCLUSIONS: Women age 60 years and younger at the time of breast cancer diagnosis who have an obesity genetic risk model are at increased risk for weight gain after treatment and should be targeted for weight‐maintenance interventions. Cancer 2017;123:2413–21. © 2017 American Cancer Society . Abstract : Weight gain after a diagnosis of breast cancer is a significant health hazard because of its impact on survival, breast cancer‐specific survival, and quality of life. Women younger than 60 years at the time of breast cancer diagnosis who have an obesity genetic risk model have an increased risk of weight gain after treatment and should be targeted for weight‐maintenance interventions.